(untitled) (Research, Society and Development, 2021)
Nowadays, the pharmacist plays a very important role, taking actions aimed at the rational use of medicines, with the pandemic, he manages the hospital pharmacy aimed at combating COVID-19 and in community pharmacies providing pharmaceutical care. The study aims to describe the professional’s performance during the pandemic. The present study is an integrative review, based on bibliographic research established through articles published on the role of clinical pharmacists in the face of COVID-19. Data collection was carried out between February and March 2021, where studies published in the following databases were investigated: Science Direct, PubMed and MEDLINE through Capes Periodicals. The role of the pharmacist in combating the coronavirus has been fundamental in guiding patients with comorbidities who seek information about drugs in the pathological process of COVID-19, supply and control of stocks of medical and hospital materials, in clinical care activities, dealing with their use safe and rational medications, preventing errors related to medications and taking care of the stability of drugs, whether after dilution or reconstitution, was fundamental for the economy and the use of scarce resources. As we are going through difficult times, the pharmacist is acting in the face of this pandemic, becoming an essential professional, since he has full support to integrate the health teams at the front, developing all his expertise regarding medicines, doses, adverse effects and drug interactions, supporting other professionals and guiding patients with pharmaceutical care.